A Contactless Receptacle Applied to DC Power Distribution - Worapong Pairindra; Surin Khomfoi (International Review of Electrical Engineering (IREE), 2021)
The modern household power distribution with dc-to-dc power transfer is presented in this paper in order to demonstrate inductive power transfer technology over air-core and ferromagnetic-core. A high-frequency switching with a five-level diode clamped multilevel converter plays an important role in generating a low-%THD voltage waveform in order to increase the power density or reduce the size of the plug and receptacle. The major setbacks of using the dc-to-dc power transfer with electric shock, galvanic isolation issue and arc discharge on the contactor have been solved by using the inductive power transfer. In addition, an LLC series resonant tank is integrated with the power converter to satisfy the Zero-Voltage Switching (ZVS) condition of all active switching devices. The proposed contactless receptacle technique is validated by using MATLAB/Simulink and a developed hardware prototype. The efficiency of the power transfer while using the magnetic material core versus the air-core type is approximately 83.8% and 92.6%, respectively.
Keywords: Wireless Power Transfer Systems; Advanced DC-DC Converters; Electrical Contact Performance and Analysis